2010
DOI: 10.1111/j.1365-246x.2010.04760.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the movements of permanently installed electrodes on an active landslide using time-lapse geoelectrical resistivity data only

Abstract: S U M M A R YIf electrodes move during geoelectrical resistivity monitoring and their new positions are not incorporated in the inversion, then the resulting tomographic images exhibit artefacts that can obscure genuine time-lapse resistivity changes in the subsurface. The effects of electrode movements on time-lapse resistivity tomography are investigated using a simple analytical model and real data. The correspondence between the model and the data is sufficiently good to be able to predict the effects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 36 publications
3
98
1
Order By: Relevance
“…Firstly, their rough surface characteristics consisting of very coarsegrained material and boulders, their small-scale topography and their high ice contents make good-quality measurements and data inversions difficult to achieve (Hilbich et al, 2009;Hauck and Vonder Mühll, 2003). Secondly, the movement of the landforms disturbs permanent installations and significantly alters the measurement geometry with time (Wilkinson et al, 2010;Loke et al, 2013). Hilbich et al (2009) demonstrated the general applicability of repeated ERT surveys for monitoring permafrost evolution on rock glaciers and highlighted the use of synthetic modelling to aid the sometimes ambiguous interpretation of the results.…”
Section: Geophysical Monitoring and Forward-inverse Modelling Cyclesmentioning
confidence: 99%
“…Firstly, their rough surface characteristics consisting of very coarsegrained material and boulders, their small-scale topography and their high ice contents make good-quality measurements and data inversions difficult to achieve (Hilbich et al, 2009;Hauck and Vonder Mühll, 2003). Secondly, the movement of the landforms disturbs permanent installations and significantly alters the measurement geometry with time (Wilkinson et al, 2010;Loke et al, 2013). Hilbich et al (2009) demonstrated the general applicability of repeated ERT surveys for monitoring permafrost evolution on rock glaciers and highlighted the use of synthetic modelling to aid the sometimes ambiguous interpretation of the results.…”
Section: Geophysical Monitoring and Forward-inverse Modelling Cyclesmentioning
confidence: 99%
“…467 with 92.07% and 91.99% of the data, respectively, having reciprocal errors smaller than 5% 500 (Wilkinson et al, 2010). Data with reciprocal errors above 5% were removed from the data set 501 before inversion.…”
Section: Movement Monitoring and Estimationmentioning
confidence: 99%
“…Noninvasive geophysical methods, which are capable of estimating physical properties of significant volumes of the subsurface, are well-suited for this application (Donohue et al, 2011). Electrical resistivity tomography (ERT) (Loke and Barker, 1996), for example, has, over recent years, been used for near-surface time-lapse imaging of natural slopes and landslides (e.g., Miller et al, 2008;Uhlenbrook et al, 2008;Cassiani et al, 2009) or, more relevant to the topic of the present work, monitoring the internal condition and temporal dynamics of geotechnical assets (e.g., Sjodahl et al, 2008, Wilkinson et al, 2011Chambers et al, 2014;Gunn et al, 2015a). Favored by the sensitivity of resistivity data to changing hydrogeological conditions, ERT, however, requires an additional stage of calibration, often site dependent, to invert for parameters more relevant to the mechanical description of the investigated target (e.g., moisture content, as in Cassiani et al, 2009;Chambers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%